(untitled) (Medical Forum Monthly, 2024)
Objective: To see the various presentation of abdominal tuberculois in surgical patients. Study Design: prospective study Place and Duration of Study: This study was carried out in the Surgical Department at civil Hospital Karachi, from Oct 2011 to 31st May 2012. Materials and Methods: Study consisted of twenty six patients. Base line and specific investigations were done in all patients, especially mantoux test, sputum examination x-ray abdomen and ultrasound of abdomen. Inclusion criteria were that all patients diagnosed as case of tuberculosis on the basis of history, clinical examination and investigations. Exclusion criteria included unfit patients for general anesthesia, pregnant ladies due to risk of foetal loss, patients with carcinoma of colon. Data was analyzed through SPSS software. Results: 26 cases of abdominal tuberculosis. 12 males (46.15%) and 14 females (53.84%). Male to female ratio was 1:1.16. Age ranged from fifteen to seventy years with mean age of patients were 42.1 years. Twelve Patients (46.15%) presented in subacute intestinal obstruction, four patients (15.38%) with acute intestinal obstruction, six (23.07%) with signs of peritonism and four (l5.38%) with mass in abdomen. Erythrocyte sedimentation was 2 patients (7.70%) had ESR 20 mm/hr, eight patients (30.77%) between 20 to 40 mm/hr, eleven patients (42.1%) between 40 to 60 mm/hr and five patients (19.23%) between 60 to 100 mm/hr. Liver Function Test was within normal range in all of them. Mantoux Test was found positive in fourteen (53.84%). Plain x-ray abdomen erect and supine position showed sixteen patients (61.54%) significant findings were observed. Barium meal and Follow through examination was performed in four patients (15.38%). Three patients (75%) showed narrowing of ileum and irregularities in the caecum and one' patient (25%) had dilated small bowel loops with narrowing of terminal part of ileum while caecum was normal. In one patient (3.84%) small bowel enema revealed delayed emptying of small bowel with dilatation of jejunum, Barium enema was performed in three cases, which revealed, filling defect in caecum and narrowing at ileocecal junction. Conclusion: We conclude that The clinical features of this disease are usually non-specific, vague and diverse therefore the accurate diagnosis is some times difficult.